Response History Analysis for the Design of New Buildings in the NEHRP Provisions and ASCE/SEI 7 Standard: Part III - Example Applications Illustrating the Recommended Methodology. Issue 2 (May 2017) - Zimmerman, Reid B.; Baker, Jack W.; Hooper, John D.; Bono, Stephen; Haselton, Curt B.; Engel, Albert; Hamburger, Ron O.; Celikbas, Ayse; Jalalian, Afshar
This paper represents the third part of a series of four publications on response history analysis for new buildings. Three real-building examples designed to a prior version of the building code are chosen, having a range of target spectrum characteristics, tectonic settings, and structural systems to test the new procedure and document its appropriate implementation. This paper describes the process of determining both MCER spectra and scenario spectra for all three examples. It explores selection of appropriate recorded ground motions and the procedure for scaling and spectrally matching to a maximum direction spectrum. Global results such as drift and treatment of unacceptable response, and local results such as force-and deformation-controlled acceptance criteria checks, are shown for each example. Practical guidance is given on implementing response history analysis for engineers employing the new Chapter 16.